Lecture-based Versus Problem-Based Learning Methods in Public Health Course for Medical Students - Hossein Jabbari; Fariba Bakhshian; Mahasti Alizadeh; Hossein Alikhah; Mohammad Naghavi Behzad (Tabriz University of Medical Sciences, 2012)
Introduction: Problem-based learning (PBL) method has progressed as an alternative to lecture-based learning (LBL) method in recent decades. Benefits of PBL clearly supported by researches however several items remain unclear especially in Iranian medical universities. The aim of this paper is to compare the learning outputs of PBL and LBL methods. Methods: In this cross- sectional study public health course was prepared for three groups of students. Group 1 included medical students (n=101), Group 2 dentistry students (n=54), and Group 3 was formed of pharmacy students (n=112). Scores of final exam as well as 10 similar- root questions as a short-term outcome, scores in national basic science exam, recent similar informal exam as a mid-term output in addition to course evaluation by students, and assessment of attitude about PBL were compared between groups. Data analysis was performed by SPSS-11 using means' comparison. Results: Scores of students in PBL group was significantly higher in final exam (P<0.001). The percentage of correct responses to 10 same- root questions in PBL (M= 6.68) were significantly higher (M=6.54). Faculty members were evaluated better in PBL group (P<0.001) in all aspects of teaching. Totally, the students who evaluated teachers in PBL group had 2 points more than LBL group (P<0.001). Scores of students in national exam (after two years) and the recent survey (in the third year) were higher in PBL group (P<0.001). Conclusion: Results of using PBL method indicated the higher rate of scores and better recalling of learned materials in this method.